TEMPORAL HYDROLOGICAL DROUGHT ANALYSIS IN LAKE IZNIK USING IN-SITU MEASUREMENTS AND SPACE-BASED DATA - Erkoc, Muharrem Hilmi; Dogan, Ugur; Keser, Busra; Bayram, Bulent (ACAD SCI CZECH REPUBLIC INST ROCK STRUCTURE & MECHANICS, 2025)
The presented study aims to monitor a potential hydrological drought in Lake & Idot;znik, one of the largest freshwater lakes in T & uuml;rkiye, located in the NW region of the country. In this context, in-situ and satellite altimetry-based water level data, meteorological data such as temperature and precipitation, and high-resolution multispectral satellite images from 2015 to 2024 have been utilized. A linear model was fitted to the water level data acquired from Turkish Directorate General for State Hydraulic Works and the altimetry-based data from HydroWeb data archive, which estimated a decreasing trend of-22.9 +/- 0.6 cm and-22.6 +/- 0.6 cm in lake water levels, respectively. The Mann-Kendall/Sen's slope trend analysis was performed on the series of temperature and precipitation data obtained from Turkish General Directorate of Meteorology, showing that there is a 0.049 degrees C increase in temperature and an annual-0.80 mm decrease in precipitation. According to the calculated temperature and precipitation values, which are increasingly high and low respectively, the hydrological drought indicators SPI and SPEI were determined to be showing an increasingly severe hydrological drought in this region. It then analyzed Sentinel-2 satellite imagery between 2015 and 2024 to determine the water surface area of the lakes with NDWI. According to Sentinel-2 images, the lake water surface area in 2023 went down by 2.7 km2 compared with that in 2015. These findings bring forth crucial implications for regional water resource management and ecosystem sustainability, placing significant emphasis on proactive measures that should be considered in order to mitigate the long-term impacts of hydrological drought in Lake & Idot;znik and its surroundings.
Keywords: Hydrological Drought; znik; Lake water level; SPEI/SPI; Hydro-Geodesy; METEOROLOGICAL DROUGHT; RIVER-BASIN; WATER; CLIMATE; VEGETATION; IMPACTS; INDEXES; Geochemistry & Geophysics; Mining & Mineral Processing